Education, Off-Farm Employment and Rural Economic Development Perspectives from States in the Southeast. Proceedings of a Rural Development Symposium at the Annual Meeting of the Southern Agricultural Economics Association (Lexington, Kentucky, February 1992) / David L. Debertin, Ed. - Debertin, David L. (Distributed by ERIC Clearinghouse, 1993)
This publication presents a series of five papers based on presentations given at a rural development symposium dealing with the role of education in off-farm employment and rural economic development. The first paper, "Education and Rural Economic Development" (Thomas G. Johnson), discusses linkages between the regional educational attainment levels and the potential for rural economic growth. Paper 2, "Investing in Government Public Services: Is it Necessary for Rural Development?" (Rodney L. Clouser), proposes specific investments by state, local, and federal governments for rural development. Paper 3, "The First Job Decision and the Probability of Off-Farm Work" (Judith I. Stallmann and James H. Nelson), reports the results of a survey related to first job decisions by farm operators and their probable consequences. The fourth paper, "Education and Economic Development in Rural Appalachia" (Thomas G. Johnson and David E. Broomhall), identifies factors that influence decisions made by high school students to obtain additional education, with a focus on the behavior of high school students in rural Appalachia. The final paper, "Human Capital, Transactions Costs and Farm Labor Supply and Demand: Some Implications for Rural Economic Development" (Stephan J. Goetz), presents an economic model of farmers' joint decision to obtain off-farm employment and to hire farm workers. This document contains numerous charts and graphs. (LP)